Management Economic Environment of Non-profit Organizations - KHORIN, Alexander N.; BROVKIN, Alexander V.; POTANINA, Yulia M. (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018, 2018)
The crisis of 2008-2009 and the decline of the gross domestic product in 2015 – 2016, showed that Russia is in a difficult and completely new stage of socio-economic development. The potential of using pre-crisis model of economic growth based on the rapid increase in lending and the growth of domestic demand, is considerably restricted. Rosstat data show that the Federal budget of Russia in 2015 was executed with a deficit of $ 1.9 trillion. rubles, or 2.6% of GDP, while in 2016 the budget deficit is projected at 2.9 trillion. rubles, or 3.5% of GDP. In addition, the reduced purchasing power of the population, which becomes a barrier to crisis exit. Thus, the decline in real income of the population of Russia in 2015-2016 is estimated at 5-6% annually. In conditions of economic turbulence, declining living standards of the population social policy is one of the core units of modern government regulation. The output state on the path of sustainable and balanced socio-economic development requires more intensive use of all resources, and transition to an innovative stage of development and modernization of the economy with the formation of adequate social infrastructure. In the framework of implementation of social policy the government is increasingly using the potential of non-profit organizations that are able, with appropriate support, to play a significant role at local, regional, and Federal levels. The nonprofit sector of the economy are the source of all sorts of social innovations, namely the non-profit organization to a great extent help in solving socially important problems, and provide the people with social services, build a dialogue between authorities and population focus of the Executive bodies on the issues of individual groups of citizens and society as a whole, form the democratic principles of organizing society. In addition, the nonprofit sector contributes to the country's GDP (about 1%) and has more than 226 thousand organizations that operate at local, regional and Federal levels, providing jobs for more than 1 % of the population. Consumers of services in the Russian nonprofit sector are more than 40 million people. However, in foreign countries, the proportion of the nonprofit sector in GDP is about 6%, while the number of people employed in the nonprofit sector about 7% of the total working population. Such low levels of participation of the Russian non-profit sector in the economy allow to speak about necessity of search for new development drivers of non-commercial organizations in Russia. Currently, there is a transformation of all aspects of the activities of the organizations of the nonprofit sector. This change of the civil legislation in part of improvement of legal forms, procedures of state registration and control of funding non-profit organizations, and taxation. Active development of the nonprofit sector is a considerable dependence on tax regulation of the nonprofit sector by providing, first of all, tax privileges and preferences, as well as from the balanced tax policy of the state against entities that are interrelated with non-profit organizations.